PEMANFAATAN TRICHOKOMPOS DAN PUPUK KANDANG SAPI UNTUK PERBAIKAN SIFAT KIMIA TANAH, PERTUMBUHAN, DAN PRODUKSI TANAMAN BAWANG PUTIH (Allium sativum L.) - Ana Aryun Rahma Astuti; Yulia Nuraini; B Baswarsiati (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2022)
The national production of garlic is currently under fluctuations and can not fulfil the demand for garlic. Farmers often face the decline of soil chemical properties that hinder plant growth and yield. Environmentally friendly fertilization alternatives are needed to overcome the problem. This study aimed to find out the effect of Trichocompost and cow manure on soil chemical properties, growth and yield of garlic plants. The results showed that the application of Trichocompost significantly affected the chemical properties of the soil. The application of various Trichocompost and cow manure combinations significantly affected the height of the garlic plant, the garlic bulb weight and the number of cloves. The coefficient correlations (r) between the soil organic C and the number of garlic cloves was 0.42, plant height was 0.26, and garlic bulb weight was 0.36. The coefficient correlations (r) between pH and garlic bulb weight was 0.60, plant height was 0,44, and the number of cloves was 0.48. The coefficient correlations (r) between total N and plant height was 0.02, garlic bulb weight was 017, and clove count was 0.10.